2020
DOI: 10.5194/esd-2020-80
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust increase of Indian monsoon rainfall and its variability under future warming in CMIP-6 models

Abstract: Abstract. The Indian summer monsoon is an integral part of the global climate system. As its seasonal rainfall plays a crucial role in India's agriculture and shapes many other aspects of life, it affects the livelihood of a fifth of the world's population. It is therefore highly relevant to assess its change under potential future climate change. Global climate models within the Coupled Model Intercomparison Project Phase 5 (CMIP-5) indicated a consistent increase in monsoon rainfall and its variability under… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
(120 reference statements)
1
5
0
Order By: Relevance
“…The present study also highlights that ISM precipitation change displays large differences between CMIP5 and CMIP6 models, which is also confirmed by results under high-emission scenarios [50]. The reasons causing the distinct ISM response between CMIP5 and CMIP6 models, especially the interhemispheric warming contrast, is worthy of further in-depth study.…”
Section: Summary and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present study also highlights that ISM precipitation change displays large differences between CMIP5 and CMIP6 models, which is also confirmed by results under high-emission scenarios [50]. The reasons causing the distinct ISM response between CMIP5 and CMIP6 models, especially the interhemispheric warming contrast, is worthy of further in-depth study.…”
Section: Summary and Discussionsupporting
confidence: 87%
“…Following an increased NH-SH warming gradient in CMIP6 compared to CMIP5 (blue and red stars in Figure 11d), the ISM precipitation also increases significantly. This suggests that the distinct ISM circulation and precipitation change between CMIP5 and CMIP6 can be largely explained by the differences in interhemispheric warming contrast, which may be further related to the enhanced Arctic warming (Figure 10b), substantially different cloud simulation, deep convective schemes in CMIP6 compared to CMIP5 [46][47]50]. Indeed, the CMIP6 models is revealed to be more capable than CMIP5 models in reproducing the spatial and temporal pattern of ISM [16], this may also contribute to some extent.…”
Section: Physical Processes For the Model Uncertaintymentioning
confidence: 91%
“…Studies revealed that the precipitation obtained from the CMIP6 models show a continuous increase compared to that of in CMIP5 models over different parts of the world, South Asian countries, particularly Zhu et al, (2020); Almazroui et al, (2020). Studies also show that CMIP6 has better skills in representing the rainfall than CMIP5 over Asia's regions (Chen et al, 2021), India (Katzenberger et al, 2021). Therefore, it is evident that the increase in precipitation is observed in both seasons under different emission scenarios (SSP2-4.5 & SSP5-8.5).…”
Section: Seasonal Mean Rainfall and Its Extreme Indicesmentioning
confidence: 96%
“…Annual monsoons are a critical source of rainfall for at least 60% of the world's population in areas including south and east Asia, Australia, and east and west Africa (Li et al 2016). The south Asian monsoon is of particular societal importance, providing 80% of the water to the subcontinent, which contains nearly a fifth of the world's population and is heavily reliant upon agriculture (Katzenberger et al 2021). In the 20th Century, a decline in the East Asian summer monsoon rains was observed, with the most intense rains becoming shorter but more intense, including flooding and droughts (Burke and Stott 2017).…”
Section: Attributable Impactsmentioning
confidence: 99%
“…In the 20th Century, a decline in the East Asian summer monsoon rains was observed, with the most intense rains becoming shorter but more intense, including flooding and droughts (Burke and Stott 2017). Since 2000, the strength of south Asian monsoon rains has increased, with the most pronounced increases occurring in the most intense events (Katzenberger et al 2021). This pattern covers all monsoon regions, to varying degrees, and crucially an associated increase in both drought and flooding Stott 2017, Wang et al 2021).…”
Section: Attributable Impactsmentioning
confidence: 99%